Analysis of equivalence of parallel variants in discrete mathematics tests - Krylovas, Aleksandras; Suboč, Olga; Kosareva, Natalja (Lietuvos matematikos rinkinys, 2021)
Different studentswere given questions in 10 variants. It was tested if all parallel variants of test questions were equivalently difficult.